2011
DOI: 10.1136/jfprhc.2011.0078
|View full text |Cite
|
Sign up to set email alerts
|

Does hormone replacement therapy cause breast cancer? An application of causal principles to three studies: Table 1

Abstract: Background Concern that hormone replacement therapy (HRT) may cause breast cancer has existed since the time it was introduced, and based on evidence in three studies, the Collaborative Reanalysis (CR), the Women's Health Initiative (WHI) and the Million Women Study (MWS), it is claimed that causality is now established. Objective To evaluate the evidence for causality in the three studies. Methods Using generally accepted causal criteria, in this paper the authors begin with an evaluation of the CR. Analogous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 37 publications
0
28
0
1
Order By: Relevance
“…Shapiro and colleagues applied causal criteria, such as biases and biological plausibility, to also assess the CR5 and MWS8 findings. Their analysis highlighted several design flaws that would potentially have skewed the findings.…”
Section: Collaborative Reanalysis Whi and Mws Critiquementioning
confidence: 99%
“…Shapiro and colleagues applied causal criteria, such as biases and biological plausibility, to also assess the CR5 and MWS8 findings. Their analysis highlighted several design flaws that would potentially have skewed the findings.…”
Section: Collaborative Reanalysis Whi and Mws Critiquementioning
confidence: 99%
“…In Part 1 of this series we evaluated the CR report,6 and concluded that it did not accord with generally accepted epidemiological principles of causation 7–9. Here, in Part 2 we apply the principles to the WHI evidence implicating E+P, firstly as reported in the clinical trial,2 1013 and then as reported in the clinical trial data combined with data from a WHI observational study that commenced at the same time 1416.…”
Section: Introductionmentioning
confidence: 99%
“…In Part 1 of this series of articles1 we have evaluated the effect of hormone replacement therapy (HRT) on the risk of breast cancer, as reported in the Collaborative Reanalysis (CR),2 and in Part 2 the effects of estrogen plus progestogen (E+P),3 as reported in the Women's Health Initiative (WHI) clinical trial and observational study 4–11. We concluded that the studies did not accord with generally accepted epidemiological principles of causation 12–14.…”
Section: Introductionmentioning
confidence: 99%